MOLECULAR IDENTIFICATION OF HYPERICUM PERFORATUM L. BY PCR AMPLIFICATION OF THE RDNA ITS REGION - Howard, C.; Bremner, P.; Fowler, M.; Slater, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The increase in usage of medicinal plant products has highlighted the necessity for authentication and quality assurance in commercial products. The development of a DNA-based method for the identification of St John’s Wort (Hypericum perforatum L.) was used as a pilot study to determine the feasibility of using DNA barcode data in the future to design simple authentication tests. The nuclear-encoded rRNA coding regions are highly conserved throughout plant species but the ITS sequences have an evolutionary rate which results in inter-species variation and intra-species conservation, and have been identified as potential DNA barcode regions. PCR primers were designed to recognise the most divergent regions of the ITS1 sequence in Hypericum species. One primer pair designed to selectively identify St John’s Wort within this region was able to discriminate H. perforatum from vouchered DNA samples of 7 different Hypericum species (DNA Bank, Royal Botanic Gardens, Kew). St John’s Wort could also be distinguished from related ornamental Hypericum species obtained from seed companies and nursery suppliers. Three commercial medicinal products claiming to contain St John’s Wort were also tested. The PCR assay identified Hypericum perforatum in only two of three commercial products at a level of detection corresponding to 0.75ng DNA (0.1% of the total genomic DNA present). The method utilised in this study has enabled the design of a rapid and reliable authentication method for St John’s Wort. This has the potential to become a model for molecular identification design, and may be reproducible in other economically valuable plants.